Interaction between skeletal muscle cells and extracellular matrix proteins using a serum free culture system - Dye, Danielle; Kinnear, B.; Chaturvedi, V.; Coombe, Deidre (2019)
© Springer Science+Business Media, LLC, part of Springer Nature 2019. The ability to grow C2C12 myoblasts in a completely defined, serum free medium enables researchers to investigate the role of specific factors in myoblast proliferation, migration, fusion, and differentiation without the confounding effects of serum. The use of defined, animal free in vitro culture systems will improve reproducibility between research groups and may also enhance translation of tissue engineering techniques into clinical applications. Here, we describe the use and characterization of a serum free culture system for C2C12 myoblasts using standard tissue culture medium and readily available, defined growth factors and supplements.